2017
DOI: 10.1080/17470218.2016.1166253
|View full text |Cite
|
Sign up to set email alerts
|

Can Gaze-Contingent Mirror-Feedback from Unfamiliar Faces alter Self-Recognition?

Abstract: This study focuses on learning of the self, by examining how human observers update internal representations of their own face. For this purpose, we present a novel gazecontingent paradigm, in which an onscreen face either mimics observersÕ own eye-gaze behaviour (in the congruent condition), moves its eyes in different directions to that of the observers (incongruent condition), or remains static and unresponsive (neutral condition). Across three experiments, the mimicry of the onscreen face did not affect ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
(92 reference statements)
1
26
0
Order By: Relevance
“…In recent years, research on the plasticity of the face representation, known as the enfacement illusion (Sforza et al, 2010), has also attracted attention (Porciello et al, 2018 for a review; Serino et al, 2015; Estudillo and Bindemann, 2017). Similar to the rubber hand illusion (RHI; Botvinick and Cohen, 1998) and the out-of-body illusion (Ehrsson, 2007), it is an approach to examine the plasticity of self-face representation using the self-other discrimination task by controlling multisensory stimulation between the self and others.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research on the plasticity of the face representation, known as the enfacement illusion (Sforza et al, 2010), has also attracted attention (Porciello et al, 2018 for a review; Serino et al, 2015; Estudillo and Bindemann, 2017). Similar to the rubber hand illusion (RHI; Botvinick and Cohen, 1998) and the out-of-body illusion (Ehrsson, 2007), it is an approach to examine the plasticity of self-face representation using the self-other discrimination task by controlling multisensory stimulation between the self and others.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…In this study, as the first step before exploring whole body topography, we developed a new task for evaluating face topography in children aged 2.5 and 3.5 years. Previous studies examining body topography in adult participants have used several perspectives for the estimation: face (Fuentes et al, 2013b; Serino et al, 2015; Estudillo and Bindemann, 2017; Mora et al, 2018; Porciello et al, 2018), hands (Longo and Haggard, 2010; Longo, 2017), and the whole body (Fuentes et al, 2013a). Many studies demonstrated interesting distortions or plasticity of face, hands, and whole body topography in adults.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the own face a unique piece of our physical identity and, therefore, the emblem of the self (McNeill, 1998). Behavioral, neurophysiological, and neuroimaging research have tried to unravel different aspects about the relevance of the own face (e.g., Tong and Nakayama, 1999; Brédart and Devue, 2006; Estudillo and Bindemann, 2016, 2017) and its different neural markers (Devue and Brédart, 2011). …”
mentioning
confidence: 99%
“…Additionally, it is possible that the effects of synchronous stimulation are short‐lived and dependent on constant stimulation, and may therefore start to decay when the SF is presented in absence of stimulation (see Ehrsson, Holmes, & Passingham, ; Estudillo & Bindemann, ), as was the case during the current target detection task. Under these circumstances, reactivating the changes in the own face representation as a consequence of multisensory stimulation might require more extensive stimulation with the SF.…”
Section: Discussionmentioning
confidence: 99%